Faktor-Faktor Yang Mempengaruhi Penggunaan Aplikasi Belanja Online Pada Masyarakat Indonesia - Anugerah Wijayaputra Japar; David Immanuel; Indra Saputra; Stevi Andreanus; Vanessa Surya (Indonesian Business Review, 2019)
Being the ongoing fad for enterprises to manage business, mobile shopping offers superior dominance over electronic shopping and traditional shopping. This paper aims to elaborate both the motive of mobile shopping response according to the theory of reasoned action (TRA) point of view and the promotion barriers in mobile business. A selfconducted survey data of 325 Indonesian consumers is led to build and apply a structural equation modeling approach with inherent constructs. Through the result of this study, the predictive power of TRA has been proven in scouting consumer response in the context of mobile shopping. In addition, the intention to adopt mobile shopping is strongly impacted by both promotion and barrier variables. Some benefits could emerge for future studies from investigating other variables (e.g. trust and risk specific aspects) and using ongoing response (e.g. online purchase). Both promotion and barrier factors should be kept under surveillance by business managers for better understanding about why and how Indonesians adopt mobile shopping. The founding study attune the TRA model with augmented promotion and barrier variables to describe mobile shopping in the context of Indonesia.